Εμμανουήλ Παπάς ο Επαναστάτης Άρχοντας ([object Object], 2015)
: and the administration of the United States of America. Thank you. Thank you. Thank you. Thank you. Thank you. Thank you. Thank you. Thank you. Ladies and gentlemen, good evening. We welcome you to the Public Academic Library tonight at the in the name of the 25th of March. I would like to especially pay tribute to the late President of Serbia, Mr. Vicido, the representative of the 10th Council, Mr. Vasile Kosta, the representative of the Church of Christ the Virgin, the presidents of the Council of Ministers, Mr. Anis Korigapos, Mr. Kozabov, the Prime Minister of Serbia, the Prime Minister of the Department of the Library, the Prime Minister of the Provincial Progressive Assembly, and I don't know who else, the representative of the Church. Thank you very much. I would like to pay tribute to the presidents of the Council of Ministers here and to all of you. As for today's announcement, one of my concerns was a trip I made one day with my car in the city of Serom and I saw a car on a road that said, in a small street, and I thought, is it possible that the name of this great patriot, this hero, has been given in a small street, does he deserve a greater honor? And so, as many times as I was given the opportunity, I tried to do something to honor this great hero more. So, in 2005 or 2006, I don't remember exactly, I was given the opportunity at the Municipal Council, I brought up the issue, because there was an issue with the school education, they were referring to one of the series, the one with the Holy Father, and nothing else. So, there I was given the opportunity, with my brothers, to make a decision, in the Municipal Council, which we promoted through the Ministry of Education, and now, at least, there is a series dedicated to the Holy Father. But I also believe in what Mr. Foukididis says about Pericles' epitaphs, that for people who were born with AIDS, it would be enough to be diagnosed with AIDS. At some point, I will start from the early days, says Pericles. It is truly fair, together with the Holy Father's epitaphs, that the Holy Father is not only a great figure, but also a great heretic, as Pericles says, who is the philopatria. The philopatria of the Holy Father was the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. So, the Holy Father is not only a great figure, but also a great heretic, who is the one that helped the Holy Father to get rid of AIDS, and to get rid of AIDS. Thank you very much. Thank you very much. Thank you very much. Thank you very much. Thank you very much. Thank you very much. Thank you very much. Thank you very much. Thank you very much. Thank you very much. Thank you very much. Thank you.